Discurso e Realidade: um Diálogo entre Hegel e Nagarjuna sobre Atos Perceptivos (Revista Eletrônica Estudos Hegelianos, 2023)
This paper’s subject matter is the dialogue between Hegel (1770-1831) and Nagarjuna (c. 150 – c. 250 CE), and it focuses on the second chapter of the Phenomenology of Spirit (1807) of Hegel—Perception, Thing, and Deceptiveness—, and the third chapter of the Fundamental Verses of the Middle Way of Nagarjuna — Examination of the Spheres or Sensory Bases (ayatana-pariksa). To do so, we will investigate the Abhidhamma in search of the relationship between ultimate and irreducible realities (dhammas) and sensory bases. This study is necessary in order to understand the context of the Nagarjunian critique of the Abhidhamma interpretation on the sensory bases and the dhammas. After these first two steps, we proceed to the study of the Hegelian interpretation of our sensory acts, noting convergences and divergences with the interpretation of the sensory bases by Nagarjuna. Finally, in the fourth and final step, we will be able to identify the formulations offered by Nagarjuna and Hegel about dependent coorigination, distinguishing characteristics of entities, and word (pratitya-samutpada, nimitta, and vac, Nagarjuna), and relation, property, and language/words (Verhalten/Verhältnis, Eigenschaft, and Sprache/Worte, Hegel), as well as about discourse’s ability to say what is real: the purpose of the dialogue built here.